Synthesis, Spectral and Antibacterial Activity of Mixed Ligand from Lanthanium (III) Complexes of Schiff Base Ligand with Some Amino Acids - Shatha M. H. Obaid (Journal of Global Pharma Technology, 2016)
In this work, lanthanium (III) complexes were synthesized using by Schiff base ligand (L) derived from benzaldehyde and o-aminoaniline with five amino acids (AA) from glycine (Gly), L-alanine (Ala), L-valine (Val), L-asparagine (Asp) and DL- phenylalanine (Phe). The Schiff base ligand has been characterized by elemental analysis, (MASS, FTIR, 1HNMR, 13CNMR, UV-VIS) electronic spectra. The structures of the new complexes have been described of analysis of elements, molar conductivity, (UV-Vis electronic, FT-IR, mass) spectra also magnetic moment. The molar conductivity values of the complexes indicat this every of complexes are electrolytes and other analytical studies reveal octahedral geometry for La (III) ion. The Schiff base ligand, five amino acids, La(III) salt and mixed ligand complexes were tested against four pathogenic bacteria such as G+- bacterial and such as G-- bacterial. These bacteria were found that compounds show, it has no effect on five amino acids and Schiff base ligand, while it has been shown to have a clear effect on lanthanum complexes.Keywords: Schiff base ligand, Amino acids, Mix ligand complexes, Spectral studies and antibacterial studies.